Finding a Route into Higher Education for Local Working Class Adults - Lyn Tett (Adult Education Research Conference, 1998)
The accessibility to adults of six Scottish HEIs and the structural and ethical factors which operate to exclude or include them are examined.How higher education might create a true access culture is assessed through a case study of one institutional response to participation barriers for working class community activists.